(untitled) (Bangladesh Journal of Medical Science, 2017)
Faced with increased threats, biomedical publishing is fortifying its publishing fortress. More rules, greater ethical standards, more verification steps, stricter penalties all seem to characterize a publishing environment that has become considerably hostile, and aggressive. It does not help that the system is being increasingly exploited by unethical individuals or groups, either intellectually or financially, and now monitored by an equally aggressive post-publication science watchdog vigilante movement. When extremes build up within a system, they create intolerable stress and at some point, the system will explode. In the past few years, biomedical publishing has witnessed several important ruptures to its integrity and a concomitant rise in the power of influence of ethical groups or organizations who have been entrusted, in some cases self-entrusted, with creating and monitoring the evolution of the ethics rules that the vast majority of biomedical academics are then expected to follow. This paper puts forward a hypothetical argument that ethics associations, or publicly acclaimed ethics specialists, are also subjected to the same corrupting forces as authors, editors or publishers. Despite this, none are being scrutinized, or being held accountable in an independently verifiable manner. Ethical power holds great marketing value for for-profit publishers. This paper examines hypothetically how ethics associations could become corrupted, could accumulate excessive power, or could manipulate rules to create a dual system of ethics to favor themselves. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.610-614